Reflection, the quadratic parent function is reflected on the opposite side
Answer:
HOPE THIS HELPS
Step-by-step explanation:
The area = length * Width.
We know the width = X+6 inches and Area = x^3+3x^2–18x.
This problem can be solved just by dividing the area by width and we get a quotient as X^2–3x.
So the length is x^2–3x inches.
No, because the sample was not random
Let us take 'a' in the place of 'y' so the equation becomes
(y+x) (ax+b)
Step-by-step explanation:
<u>Step 1:</u>
(a + x) (ax + b)
<u>Step 2: Proof</u>
Checking polynomial identity.
(ax+b )(x+a) = FOIL
(ax+b)(x+a)
ax^2+a^2x is the First Term in the FOIL
ax^2 + a^2x + bx + ab
(ax+b)(x+a)+bx+ab is the Second Term in the FOIL
Add both expressions together from First and Second Term
= ax^2 + a^2x + bx + ab
<u>Step 3: Proof
</u>
(ax+b)(x+a) = ax^2 + a^2x + bx + ab
Identity is Found
.
Trying with numbers now
(ax+b)(x+a) = ax^2 + a^2x + bx + ab
((2*5)+8)(5+2) =(2*5^2)+(2^2*5)+(8*5)+(2*8)
((10)+8)(7) =(2*25)+(4*5)+(40)+(16)
(18)(7) =(50)+(20)+(56)
126 =126